Pengembangan Kapasitas Buruh Migran Melalui Pelatihan Pembuatan Produk Kreatif Kewirausahaan - Kokom Komariah; Suyanto Suyanto; Marwanti Marwanti (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2019)
Indonesia is one of the country which has its residents migrates overseas. Indonesian Migrant Labors reflects the nation, but in reality they came from the less educated and less skilled part of the Indonesian population. The aim of this activity is to give insight, experience, and accompaniment toward the female workforces in Hong Kong in order to develop their skills in creating creative food processing products that will become their provisions in entrepreneurship. The target of this activity is the Indonesian Migrant Labors in Hong Kong of 200 people. Methods of activity consist of lectures, brain-storming, discussion, games, demonstration, and direct practices to create food products of “bakso” and “tekwan”. Steps of Activity consist of preparation, execution, and evaluation. This Community Service was successfully performed by improving the materials of entrepreneurship motivation, entrepreneurship creativity, designing business development, and practices of making various products of bakso and tekwan. The reflection result showed that this activity truly helped the participants in improving their confidence, knowledges, and insights, useful as a business provision when they come back to Indonesia, and also became their medium for self-improvement so they have a skill to be proud of. The responses of participants toward the training activity is on the very good category, shown by the material aspect, program targets, time efficiency, instructor’s ability, means, staff services, and benefits for the participants.